Target acceleration method for analysis of RC structures. Issue 8 (2nd November 2015) - Balic, Ivan; Mihanovic, Ante; Trogrlic, Boris
Abstract : Purpose: – The purpose of this paper is to present a new modification of the multimodal pushover method, named the target acceleration method. The target acceleration is the minimum acceleration of the base that leads to the ultimate limit state of the structure, i.e., the lowest seismic resistance. Design/methodology/approach: – A nonlinear numerical model is used to determine the target acceleration, which is achieved using the iterative procedure according to the envelope principle. Validation of the target acceleration method was conducted on the basis of the results obtained by incremental dynamic analysis. Findings: – The influence of higher modes is highly significant. The general failure vector corresponding to the target acceleration differs from the first load vector and the form of the load with uniform acceleration according to the height of structure, as contained in the European Standard EN 1998-1. Comparison between the target acceleration, including the equivalent structural damping, and the failure peak ground acceleration obtained from the dynamic response of the structure exhibits notably good agreement. This result implies that the equivalent structural damping as calculated according to the formulation presented in this paper should be greater than that suggested in the literature. Originality/value: – The originally developed procedure named multimodal pushover target acceleration method can reasonably estimate the minimum acceleration of the base that leads to the ultimate limit state of the structure, and consequently provides a reliable tool for the assessment of the lowest seismic resistance.